Training On Making Cooperation in Business Investment at Moji Grill : Pelatihan Pembuatan Kerjasama Dalam Penanaman Modal Usaha Pada Kedai Moji Grill - Hasanah; Husainah, Nazifah; Hanifah, Azimah; Sunarti (Procedia of Social Sciences and Humanities, 2022)
Kedai Moji Grill was initiated by three young people who have creative minds in finding current business opportunities. This business is motivated by their desire to increase their income (the Covid 19 condition) has decreased, this happens because most of them work the WFH way. Starting with chatting with the three of them and finally they have an idea, how they can open a culinary (food) business that has contemporary values with the aim of attracting young consumers, the business was founded with limited capital with shared capital. Finally, the three of them created their business by renting a place (parking a shophouse) in the Kampung utan Ciputat area, South Tangerang. They open their business from 17.30 - 10.00 WIB by using a tent. The problems that exist are; does not yet have the right way to distribute profits or losses to investors; Still using tents in running their business; There is still 1 variant of food offered to consumers. The solutions offered to moji grill shop entrepreneurs are: Helping provide training in making cooperation in business investment. The results of the implementation of abdimas to partners is to conduct training to the initiators of the business, namely Aulia Hazmi Ramadhan, Bimo Aulia Utomo, Abduel Surahman, and one employee, namely Dede Maulana. The training provided is training in making cooperation in investment in the Moji Grill business. Currently the business is preparing to open a new branch with the entry of new investors who are interested in the busines.